The ability of crude oil degradation and bio-surfactant production by an yeast strain (1214-bk14) isolated from producing oil well at white tiger oil field, Vung Tau, Vietnam - Quynh Hoa, Kieu Thi; Yen, Nguyen Thi; Yen, Dang Thi (Academia Journal of Biology, 2016)
The interest in microbial surfactants has been steadily increasing in recent years, as the microbial surfactants have numerous advantages compared to chemical surfactants, such as a lower toxicity, better environmental compatibility and effective properties at extreme temperature, pH levels and salinity. A highly biosurfactant-producing strain of yeast, 1214-BK14 was selected among the isolated strains from producing oil wells at White Tiger oil field in Vung Tau, Vietnam. The identification using API 20C AUX showed that the 1214-BK14 strain similar 99% with Cadida tropicalis. The suitable condition for the biosurfactant production by the strain 1214-BK14 were found to be 37oC, pH6, 4% and 0,45% (w/v), for temperature, initial solution pH, intitial concentration of carbon substrate (crude oil), and intitial concentration of nitrogen substrate ((NH4)2SO4), respectively, and the emulsification index (E24) measured in the conditions was 71%. The total crude oil and C10 - C43 alkanes degradation efficiency by the strain 1214-BK14 estimated using GC/MS were 83,37% and 74,54-97,46%, respectively. These results revealed that the strain 1214-BK14 exhibited a tremendous potential for contaminated-crude oil degradation and microbial enhanced oil recovery (MEOR).